Fixed bed adsorption for wastewater treatment - Muhammad Mutammimul Ula, W. Abd. Latif (2012)
This study is about the comparison of flow arrangement in fixed bed adsorption for wastewater treatment and also to study the equilibrium adsorption in batch mode,to study the column adsorption for dye removal,and to study the effect of flow pattern,flow rate and initial dye concentration.The adsorption of methylene blue from wastewater onto granular activated carbon (GAC) in fixed bed was investigated and breakthrough data of the dyes was determined.This research is run in small scale column at constant temperature and pH value.The equilibrium study was done on batch mode and the data fitted with Langmuir model so that the design parameter will be evaluated.The column mode was studied by considering varies parameter to find suitable flow pattern (up-flow and down-flow) and optimum flow condition.Both the flows will be subject to static mode adsorption studies.The effects of bed height,initial concentration and flow rate on breakthrough curve were investigated.It is found that breakthrough time and adsorption capacity increases by increasing flow rate, increasing initial concentration and decreasing bed height. The results show that the up-flow arrangement is better performance than the down-flow arrangement.This is due to the higher of the breakthrough time and the equilibrium capacity for up-flow column in all experimental conditions.